2022
DOI: 10.3390/antiox11071376
|View full text |Cite
|
Sign up to set email alerts
|

Adenophora Stricta Root Extract Protects Lung Injury from Exposure to Particulate Matter 2.5 in Mice

Abstract: Chronic exposure of particulate matter of less than 2.5 μm (PM2.5) has been considered as one of the major etiologies for various respiratory diseases. Adenophora stricta Miq. is a medicinal herb that has been used for treating respiratory diseases in East Asia. The present study investigated the effect of A. stricta root extract (AsE) on PM2.5-induced lung injury in mice. Oral administration of 100–400 mg/kg AsE for 10 days significantly reduced the PM2.5-mediated increase in relative lung weight, but there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(65 citation statements)
references
References 54 publications
(68 reference statements)
4
56
0
Order By: Relevance
“…When body weights were measured on days 0, 1, 7, 14, 15, and 16, there were also no differences in the body weight between vehicle, OVA, and OVA + AsE groups. However, DEXA significantly reduced the body weight from day 7 onward, which was parallel with previous reports that DEXA reduces body weight probably due to muscle atrophy [ 16 , 17 , 20 , 21 ]. Consistently, there were no differences in the body weight gains between the vehicle, OVA, and OVA + AsE groups during the entire experimental period, and DEXA significantly decreased the body weight gain ( Figure 1 a).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…When body weights were measured on days 0, 1, 7, 14, 15, and 16, there were also no differences in the body weight between vehicle, OVA, and OVA + AsE groups. However, DEXA significantly reduced the body weight from day 7 onward, which was parallel with previous reports that DEXA reduces body weight probably due to muscle atrophy [ 16 , 17 , 20 , 21 ]. Consistently, there were no differences in the body weight gains between the vehicle, OVA, and OVA + AsE groups during the entire experimental period, and DEXA significantly decreased the body weight gain ( Figure 1 a).…”
Section: Resultssupporting
confidence: 90%
“…We recently reported that AsE contains vanillic acid 4-β-D-glucopyranoside (VA-4G) [ 16 ]. After column chromatography was additionally performed to purify other bioactive compounds of AsE, 2-furoic acid (FA) and 5-hydroxymethylfurfural (HMF) were further identified by nuclear magnetic resonance spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations